2013
DOI: 10.1093/cid/cit123
|View full text |Cite
|
Sign up to set email alerts
|

A Serologic Correlate of Protective Immunity Against Community-Onset Staphylococcus aureus Infection

Abstract: Cutaneous S. aureus infection does not reliably provoke durable, protective immune responses. This study provides the first link between protection from disease recurrence and the humoral response to Hla, a virulence factor already implicated in disease pathogenesis. These observations can be utilized to refine ongoing vaccine and immunotherapy efforts and inform the design of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 40 publications
7
128
1
Order By: Relevance
“…Evidence is available suggesting the importance of antibodies in controlling S. aureus infections: in vitro and in vivo antibodydependent protection have been reported for S. aureus antigens (20)(21)(22)(23), antibody titers against S. aureus have been shown to rise during infections (24), and immunoglobulin deficiencies were related to an increase in susceptibility to the pathogen (25). Nevertheless, limited correlations have been established between antibody levels and disease severity or protection (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is available suggesting the importance of antibodies in controlling S. aureus infections: in vitro and in vivo antibodydependent protection have been reported for S. aureus antigens (20)(21)(22)(23), antibody titers against S. aureus have been shown to rise during infections (24), and immunoglobulin deficiencies were related to an increase in susceptibility to the pathogen (25). Nevertheless, limited correlations have been established between antibody levels and disease severity or protection (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous drug users without endocarditis were more frequently antibody positive (Ͼ3.2 IU/ml; 44%) than were those with endocarditis (6%; P ϭ 0.01) (48). The most compelling data that anti-alphatoxin antibodies correlate with protection from S. aureus disease came from a recent report by Fritz et al (51). The data from that study showed that symptomatic subjects colonized with S. aureus exhibited the highest mean baseline Ab titers against alpha-toxin (P ϭ 0.002) and that patients with invasive S. aureus infections had the lowest preexisting Ab titers against alpha-toxin or LukF.…”
Section: Figmentioning
confidence: 99%
“…Twelve distinct alpha-toxin sequence types were identified from the 197 hla-positive isolates, and MEDI4893 neutralized alpha-toxin produced by all 12 different variants. Based on these observations, the correlation of higher anti-alpha-toxin antibody levels to better clinical outcomes in epidemiological studies (36,48,51) and the efficacy of alpha-toxin MAbs or vaccines in animal models (27,(32)(33)(34), we have initiated a phase 2 clinical trial with MEDI4893 to prevent ventilator-associated S. aureus pneumonia. Further studies are under way to verify these observations among S. aureus pneumonia patients.…”
Section: Figmentioning
confidence: 99%
“…25 In addition, long-term follow-up of children with invasive S. aureus disease reveals a protective association between anti-a-toxin antibody titers and recurrent infection. 26 PVL is a pore-forming cytotoxin consisting of 2 subunits, LukS-PV and LukF-PV, which cause leukocyte destruction and tissue necrosis. 27 Although produced by <5% of S. aureus strains, a large proportion of methicillin-resistant (MRSA) strains that cause invasive community-acquired infections such as necrotic skin and soft-tissue infections and necrotizing pneumonia are positive for the PVL gene.…”
Section: Introductionmentioning
confidence: 99%